ANALISIS PENGENDALIAN KUALITAS PIPA MARINE HOSE PADA PT YOKOHAMA INDUSTRIAL PRODUCTS MANUFACTURING INDONESIA - Kurniawan, Nur Indra; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2025)
This study explores the impact of integrating Failure Mode and Effect Analysis (FMEA) and Root Cause Analysis (RCA) on marine hose quality at PT Yokohama Industrial Products Manufacturing Indonesia. Driven by a defect rate that exceeded the 5% threshold (5.13% from June 2024 to May 2025), the research employed a descriptive quantitative design, using observation, documentation, and interviews. Among 937 defective units, surface cracks (468 cases, 39.8%), joint leaks (281 cases, 23.4%), and pipe deformations (188 cases, 15%) were most prevalent. FMEA assigned Risk Priority Numbers (RPNs), identifying cracking (RPN = 270), leakage (240), and deformation (144) as top risks. RCA with the 5 Whys revealed root causes: irregular vulcanization machine calibration, substandard raw materials, and inconsistent temperature control. Following corrective measures scheduled calibrations, raw material verification, and standardized vulcanization processes the defect rate dropped significantly. Over three months, defective units fell from 243 to 97 (a 40% reduction), and RPNs decreased: cracking to 120 (−55.6%), leakage to 90 (−62.5%), and deformation to 60 (−58.3%). These results confirm that combining FMEA and RCA effectively reduces failure risk, enhances product quality, and improves manufacturing efficiency.